The development of financial markets in Africa: trends, challenges and prospects - Mutize, Misheck; Tefera, Ejigayhu; Nkhalamba, McBride (Journal of Economics and Behavioral Studies, 2020)
This paper explores trends and challenges in the development of African financial markets over the past two decades. Access to capital is essential for government to finance its budget and the performance of government policies is in part evaluated through how financial asset prices respond to the policy choices. Erratic security issuance, thin trading, low turnover ratios and lack of market depth has characterised African financial markets as inefficient. Applying a descriptive research model on key data from international think tanks to observe the behaviour of financial markets data in African countries, the study finds that African financial markets still face the traditional challenge of lack of market depth relative to other regions in other continents due to their limit size and very low market capitalisation. This is a key factor holding back the ability of investors to exploit expansion opportunities. This paper recommends that, part of the solution to challenges faced by African financial markets is for governments to assist in set-up electronic trading platforms, improve trading and settlement infrastructure.